2021
DOI: 10.3389/fonc.2020.565384
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Single-Arm Study of Apatinib and Oral Etoposide in Heavily Pre-Treated Metastatic Breast Cancer

Abstract: IntroductionWe performed this clinical trial to evaluate the efficacy and safety of apatinib and oral etoposide in patients with HER2-negative locally advanced or metastatic breast cancer (MBC).MethodsPatients with HER2-negative MBC previously treated with anthracycline and taxanes and failed ≥1 prior chemotherapy regimens were recruited. The starting dose of apatinib was 500 and 425 mg in patients with ECOG scores of 0–1 and 2, respectively. The etoposide capsules were given at 50 mg/m2 on days 1 to 10 for 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Hopes are pinned on the combination of apatinib and other drugs. In 2020, a phase II trial showed that apatinib combined with etoposide capsules is effective and tolerable in heavily pretreated, metastatic HER2-negative breast cancer patients (53). Another phase II trial showed that the ORR of an apatinib plus PD-1 inhibitor regimen was markedly higher than the previously reported ORR of anti-PD-1/PD-L1 antibody or apatinib monotherapy in advanced TNBC (54).…”
Section: Breast Cancermentioning
confidence: 99%
“…Hopes are pinned on the combination of apatinib and other drugs. In 2020, a phase II trial showed that apatinib combined with etoposide capsules is effective and tolerable in heavily pretreated, metastatic HER2-negative breast cancer patients (53). Another phase II trial showed that the ORR of an apatinib plus PD-1 inhibitor regimen was markedly higher than the previously reported ORR of anti-PD-1/PD-L1 antibody or apatinib monotherapy in advanced TNBC (54).…”
Section: Breast Cancermentioning
confidence: 99%
“…Oral etoposide was assessed as a valuable and safe option for pre-treated MBC patients [89,90]. Moreover, etoposide with apatinib has been reported to be effective and tolerable in heavily pretreated, metastatic HER2 − negative breast cancer patients [91]. On the other hand, etoposide in combination with irinotecan in a Phase II trial for refractory MBC, was terminated as the interim analysis revealed severe toxicity effects [92].…”
Section: Drugs Known To Target Cd82 Tyrosine Kinase Inhibitors (Tkis)mentioning
confidence: 99%
“…Among 38 patients with advanced non-TNBC [ 6 ], apatinib acquired a median PFS and OS of 4.0 months and 10.3 months, respectively. In addition, the retrospective analysis results revealed that metastatic breast cancer patients had comparable results compared with other trials [ 15 , 16 , 17 , 18 , 20 , 21 , 32 , 33 ] after treatment with apatinib. The median PFS and the OS were 4.7 and 15.4 months, respectively, and the longer period than patients in prior chemotherapy alone studies [ 3 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] suggested that apatinib may be used to treat individuals who have developed multidrug resistance to traditional chemotherapy medicines, while the ORR and the DCR were 22.7%, and 80.5%, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…In recent years, apatinib was used for treating breast cancer and showed a good clinical benefit in both triple negative and non-triple-negative metastatic breast cancer [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, whether in clinical trials and real-world studies, high doses of 500 mg or 425 mg are often chosen for treatment, resulting in an inability to tolerate grade III hypertension and proteinuria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation